Chromosomal characteristics of the temperate notothenioid Wsh Eleginops maclovinus (Cuvier). - Mazzei, F.; Ghigliotti, L.; Coutanceau, Jean-Pierre; Detrich, W.H; Prirodina, F.; Ozouf-Costaz, Catherine (HAL CCSD, 2008)
International audience